Factor influence the intention in buying organic food among students in Universiti Malaysia Kelantan. - An Nur Nabila Ismail. (2017)
The purpose of the research was to examine the factor influence purchasing behavior towards organic food among students in Universiti Malaysia Kelantan. In this study, quantitative approach was used and 367 respondents have been selected from Universiti Malaysia Kelantan students. The questionnaires were distributed to the Universiti Malaysia Kelantan students to gather the necessary information. After all data has been collected, the researcher analyzes data using SPSS and interpreted in the diagrams view. In general, bases on past study, the factor that influence consumer to buy organic food are health concern, food safety, environmental concern and the knowledge about organic food.